Pekarangan sebagai Lumbung Keanekaragaman Hayati: Studi Etnobotani Tumbuhan Pekarangan di Desa Wajak Kabupaten Malang - Adinda Afifatul Husna; Bening Intan Vandiasty; M. Atya Nauqa; Fahrul Ghani Muhaimin; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
Yards play an important role as biodiversity reservoirs that support the community's food, health, economic, and local knowledge preservation needs. However, information on the types and patterns of yard plant utilization based on local knowledge is still limited, especially in Wajak Village, Malang Regency. This study aims to identify the diversity of yard plants and their utilization, and to analyze the quantitative ethnobotanical index based on the community's local knowledge. The method used is a mixed methods with exploratory sequential design. Qualitative data were obtained through observation and semi-structured interviews with 11 informants, as well as documentation, while quantitative data were obtained from 98 respondents through questionnaires. The results showed that there were 19 species of yard plants used as food, traditional medicine, animal feed, building materials, and economic resources, with herbaceous habitus as the most dominant. The highest ICF value of 0.99 indicates a strong agreement among communities in the utilization of yard plants. The highest RFC value of 1 was possessed by 17 species, including Cucumis sativus, Zea mays, and Zingiber officinale. The highest SUV value was found in Cucumis sativus at 5.09. The Cucurbitaceae family had the highest FUV value at 5.09. The most widely used plant part was the fruit, with a PPUV of 30.09%. A FL value of 100% was found for Brassica oleracea, Brassica juncea, and Vigna sinensis in the processed and cooked categories, indicating strong specificity of use. This study concludes that the use of yard plants in Wajak Village is diverse, multifunctional, and supported by strong local knowledge passed down through generations.